Privatisation reforms and health work in schools: the end of the beginning. Issue 2 (3rd March 2020) - Thorburn, Malcolm
ABSTRACT: This discursive paper selectively reviews the empirical papers informing the major part of the special issue. In doing so it focuses particularly on issues which are apparent across many papers. One major point of contrast is the advanced state of marketisation in schools situated at the lower socioeconomic margins. This is relative to those schools in more socially advantaged areas where a more selective and rather insular and individual approach to privatisation engagement was noted. Bisecting this encroaching, namely cosy, continuum was further unease about the construction of curriculum arrangements and the precise position teachers' level of expertise held within these provisions. While applauding the insightful advances in understanding the empirical papers in the special issue have yielded, the paper concludes by arguing for a more expansive and wider engagement with social and economic theory if health work in schools is to progress further and reach beyond its current end of the beginning stage of development.